1997
DOI: 10.1097/00007632-199712150-00020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Specific Stabilizing Exercise in the Treatment of Chronic Low Back Pain With Radiologic Diagnosis of Spondylolysis or Spondylolisthesis

Abstract: A "specific exercise" treatment approach appears more effective than other commonly prescribed conservative treatment programs in patients with chronically symptomatic spondylolysis or spondylolisthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
525
0
37

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 964 publications
(594 citation statements)
references
References 51 publications
24
525
0
37
Order By: Relevance
“…The presence of paraspinal muscle changes in people with spondylolisthesis, as it was shown in the present study, provides further understanding of the possible mechanisms for efficacy of exercise in interventions in LBP. For instance, O'Sullivan et al [42] reported good clinical efficacy (decreased pain intensity and functional disability) of specific training of muscles surrounding the spine in individuals with spondylolysis and spondylolisthesis. Our data that also show a relationship of FJOA (multifidus and erector spinae) and disc space narrowing (erector spinae) with muscle changes provides justification for trials of training in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of paraspinal muscle changes in people with spondylolisthesis, as it was shown in the present study, provides further understanding of the possible mechanisms for efficacy of exercise in interventions in LBP. For instance, O'Sullivan et al [42] reported good clinical efficacy (decreased pain intensity and functional disability) of specific training of muscles surrounding the spine in individuals with spondylolysis and spondylolisthesis. Our data that also show a relationship of FJOA (multifidus and erector spinae) and disc space narrowing (erector spinae) with muscle changes provides justification for trials of training in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…O'Sullivan et al [42] found that individuals with chronic LBP and a radiological diagnosis of spondylolysis or spondylolisthesis who underwent a 10-week specific exercise treatment program involving the specific training of the deep abdominal muscles, with co-activation of the lumbar multifidus proximal to the pars defects showed a statistically significant reduction in pain intensity and functional disability levels, which was maintained at 30-month follow-up. The control group that received treatment as directed by their treating practitioner showed no significant change in these parameters after intervention or at follow-up.…”
Section: Stabilization Exercisesmentioning
confidence: 99%
“…Although the link between posture and back pain is largely unknown, it has been speculated that end-of-range sitting and standing postures, that were shown to be associated with altered muscle activation patterns [1][2][3][4][5], may result in excessive loading of the passive spinal structures, eventual trauma and injury and could potentially pose a risk to the development of back pain [4,6]. Postural re-education is performed on the premise of optimizing spinal alignment to minimize stresses on the spinal structures and to improve trunk muscle efficiency in protecting the spine [7][8][9][10]. Objective evaluation of postures has traditionally been an important element of clinical assessment and evaluation of the effectiveness of postural re-training.…”
Section: Introductionmentioning
confidence: 99%
“…Objective evaluation of postures has traditionally been an important element of clinical assessment and evaluation of the effectiveness of postural re-training. In addition, objective evaluation of postural patterns is used clinically to sub-classify patients into specific motor control impairment sub-groups to guide intervention [10][11][12].…”
Section: Introductionmentioning
confidence: 99%